Nuclear shuttling of CDC4 mediated broad-spectrum antiviral activity against diverse coronaviruses - Mingwei Li; Yang Wu; Jin Tian; Qian Yang; Mingze Gao; Yongrui Wang; Xuepeng Wang; Ju Zhang; Yudi Pan; Hongyan Shi; Da Shi; Xin Zhang; et al. (Emerging Microbes and Infections)
Pandemics of coronavirus (CoV)-related infection have been a major issue since the outbreaks of SARS, MERS and COVID-2019 in the past decades, leading a substantial threat to public health. Porcine deltacoronavirus (PDCoV), a new swine coronavirus, causes enteropathogenic disease characterized by acute diarrhoea, vomiting and dehydration in suckling piglets and poses potential risks of cross-species transmission. Here we reveal a novel function of CDC4 protein in restricting PDCoV infection. Ectopic expression of CDC4 suppresses PDCoV replication, whereas knockdown of CDC4 expression enhances PDCoV infection. Importantly, it was revealed that PDCoV encoded nucleocapsid (N) was involved in CDC4 nuclear-cytoplasmic shuttling, which was critical for CDC4 to exert the antiviral activity against PDCoV replication. Mechanistically, PDCoV N protein was detected to specifically interact with RIG-I to antagonize RIG-I-like receptor (RLR)-mediated IFN-β production, leading to disruptions of host innate immune defense. Meanwhile, CDC4 was proved to interact with PDCoV N protein and disrupted the interaction between PDCoV N and RIG-I, resulting in alleviated antagonism of IFN-β production mediated by PDCoV N. Similarly, a broad-spectrum inhibitory effects of CDC4 on N mediated antagonism were confirmed by the shared mechanisms among the different coronaviruses from Coronaviridae family, such as transmissible gastroenteritis virus (TGEV) from Alphacoronavirus (α-CoV) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from Betacoronavirus (β-CoV). Therefore, a novel antiviral role of CDC4 was elucidated that CDC4 competes binding with CoVs N proteins to suppress CoVs N mediated antagonism of RLR associated signalling pathway in the context of diverse coronavirus infections.